Larval morphologies of three species of stream toads, genus Ansonia (Amphibia: Bufonidae) from East Malaysia (Borneo), with a key to known Bornean Ansonia tadpoles - Haas, A.; Wolter, Johanna; Hertwig, Stefan T.; Das, I. (Magnolia Press, 2009)
We describe the external morphology of tadpoles of Ansonia longidigita Inger, 1960, A. minuta Inger, 1960, and A. platysoma Inger, 1960 from East Malaysia, Borneo. Specimens were collected from small to medium-sized streams with swift current in Sarawak State. Tadpole identities were confirmed by matching tadpole genetic sequences (16S mtRNA) to sequences from adult toads from the same collection sites. Among the three species, A. minuta appears to prefer the strongest current and was collected from fast-flowing waters in association with boulders. Ansonia longidigita larvae inhabit more moderate currents than sympatric A. platysoma. Species microhabitat choices are reflected in their body shape, with A. minuta and A. platysoma being more streamlined than A. longidigita. Colour photos of live specimens and a key to the known Bornean Ansonia tadpoles are provided to facilitate field identification.